Animal models of myocardial infarction: Mainstay in clinical translation - Kumar M.; Kasala E.R.; Bodduluru L.N.; Dahiya V.; Sharma D.; Kumar V.; Lahkar M. (My University, 2025)
Preclinical models with high prognostic power are a prerequisite for translational research. The closer the similarity of a model to myocardial infarction (MI), the higher is the prognostic value for clinical trials. An ideal MI model should present cardinal signs and pathology that resemble the human disease. The increasing understanding of MI stratification and etiology, however, complicates the choice of animal model for preclinical studies. An ultimate animal model, relevant to address all MI related pathophysiology is yet to be developed. However, many of the existing MI models comprising small and large animals are useful in answering specific questions. An appropriate MI model should be selected after considering both the context of the research question and the model properties. This review addresses the strengths, and limitations of current MI models for translational research. © 2016 Elsevier Inc.